1999
DOI: 10.1037/0097-7403.25.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Blocking in the spatial domain with arrays of discrete landmarks.

Abstract: A characteristic feature of associative conditioning is that learning a predictive relationship between two events can block later learning about an added event. It is not yet well established whether blocking occurs in the spatial domain or the circumstances in which it does. We now report, using rats trained to search for hidden food near landmarks in an open field arena, that blocking can occur in spatial learning. The animals noticed the added landmark at the start of the blocking phase and explored it, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 40 publications
(54 reference statements)
3
61
2
1
Order By: Relevance
“…Learning relative to a local landmark has been shown to follow the predictions of associative reinforcement learning (10). By contrast, we predicted that boundary-related learning would be incidental, for two reasons.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Learning relative to a local landmark has been shown to follow the predictions of associative reinforcement learning (10). By contrast, we predicted that boundary-related learning would be incidental, for two reasons.…”
mentioning
confidence: 64%
“…However, spatial learning, a crucial aspect of daily life, has long been proposed to exemplify a qualitatively different type of learning (6,7), whereby ''incidental'' and ''latent'' learning occur independent of reinforcement. Perhaps surprisingly, formal demonstration that spatial learning deviates from the predictions of associative reinforcement, given the additional assumption that exploration can be rewarding in itself, has not been forthcoming (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…This was true regardless of whether the location of the cues was fixed or variable and despite the fact that the location of the reinforcer was predictable from the position of a single cue under every condition. In a follow-up experiment using similar methods, Biegler and Morris (1999) demonstrated that the spatial arrangement of the cues was more important to finding the reinforcer than the physical features of the cues themselves. Performance was unimpaired when some of the cues were rearranged, as long as the spatial arrangement remained intact and continued to predict the location of the reinforcer.…”
Section: Org Downloaded Frommentioning
confidence: 99%
“…distal cues) and responses (e.g. approach behaviors) and it is assumed that place learning follows similar rules of acquisition to those operating in classical and instrumental conditioning [5,14]. Associative explanations of novel, or flexible, spatial behaviors are typically limited to those based upon stimulus generalization and do not involve appeals to representations such as a cognitive map, although spatial behaviors may come under the control of potentially complex stimulus relationships or configurations [30,35].…”
Section: Introductionmentioning
confidence: 99%